2004
DOI: 10.1002/jmri.10441
|View full text |Cite
|
Sign up to set email alerts
|

Wall shear rates differ between the normal carotid, femoral, and brachial arteries: An in vivo MRI study

Abstract: Purpose:To investigate wall shear rates in vivo in the common carotid, brachial, and superficial femoral arteries using very high resolution magnetic resonance imaging (MRI) phase contrast measurements. Materials and Methods:Mean, maximum, and minimum wall shear rate and an oscillatory shear index were measured for 20 volunteers, aged 23.3 Ϯ 1.9 years, in the three arteries, using phase contrast imaging with 0.0625 mm 2 resolution and three-dimensional paraboloid fitting. Results:The superficial femoral artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
93
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 28 publications
6
93
1
2
Order By: Relevance
“…18 Finally, the relationship observed only in the femoral artery could be attributed to the fact that this artery has increased oscillation in wall shear rates than other arteries, 27 which increases the propensity to atherosclerotic events in this artery bed. 27,28 The relationship between blood flow and markers of inflammation in the active group was not expected. However, several studies have shown that exercise does not always results in favorable improvements in plasma levels of hsCRP.…”
Section: Discussionmentioning
confidence: 93%
“…18 Finally, the relationship observed only in the femoral artery could be attributed to the fact that this artery has increased oscillation in wall shear rates than other arteries, 27 which increases the propensity to atherosclerotic events in this artery bed. 27,28 The relationship between blood flow and markers of inflammation in the active group was not expected. However, several studies have shown that exercise does not always results in favorable improvements in plasma levels of hsCRP.…”
Section: Discussionmentioning
confidence: 93%
“…13 Interestingly, in humans, the mean SS varies between 0.05 and 0.76 Pa in the veins, 0.3 and 0.7 Pa in the peripheral arteries (eg, the brachial artery, the femoral artery), and 1.0 and 1.5 Pa in the central arteries (eg, the carotid artery). [14][15][16][17][18] Due to the ubiquitous presence of endothelium in the blood vessels of all calibers, the constant exposure of these cells to SS, and their sensitivity to interaction with other celladhesion molecules, vascular endothelium could be targeted for systemically administered NP-based therapies. 12,19 There are different classes of NP available for biomedical applications.…”
mentioning
confidence: 99%
“…WSS have been intensively used to investigate the correlation with atherosclerosis all the way back to the first studies by [3] and [4]. Although there have been attempts to estimate WSS from direct flow measurements [5] the process is still inherently hampered with the need to make critical assumptions on the flow profile and three dimensional phase contrast magnetic resonance imaging (PC-MRI) velocity measurements lack the necessary resolution in the near wall region. Thus, there are currently no non-invasive methods that can reliably be used to compute WSS directly to study or monitor the progress of the atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%